Unlocking the potential of the local fruit peels in Malaysia as bioserbants - Hamid, Anis Hamizah; Mohd Salim, Rosliza; Ahmad Fadzillah, Nurrulhidayah (Akademi Pengajian Islam Kontemporari Universiti Teknologi MARA 40450 Shah Alam, Selangor, MALAYSIA, 2024)
The local fruit such as durian, jackfruit and banana are the common commercial fruits in Malaysia throughout year. According to Agriculture and Food Security Deputy Minister, Malaysia produced 455,458 metric tons of durian in 2022 and soon expected to increase up to 505,853 metric tons by 2025 (The Sun, Feb 2024). However, the edible flesh from these commercial local fruits is only about 15-30 % while another 70-85 % are the peels would be thrown away (Mohamed, Najib & Muniandi, 2012). Therefore, the Malaysian local fruit peels become overflowing agricultural waste that disposed either by individual in small scale or large scale by the food industry. Recently, scientists are very interested to study about the biosorbents from fruit peels waste that abundantly available from the agricultural and food processing industry (Nematollahzadeh & Vaseghi, 2022). Biosorbent is a substrate that can remove pollutants which sources can be from microbial biomass, seaweeds, food waste and also agricultural waste and other materials (Hussein et al., 2022). This innovation in future can transform the waste into wealth through fruit peels. The peels as the outer protective layer of these fruits contain a lot of fiber and can be potentially developed as organic adsorbents (Pathak, Mandavgane and Kulkarni, 2015). Not only low in cost, the organic adsorbent from fruits peels materials appears as abundant in nature, eco-friendly and biodegradable. The remedy from these fruit peels adsorbent with simple alkaline treatment and drying processes will give distinctive effect to adsorb lubricant oil waste. The idea to reuse fruit waste to reduce oil waste is a mission that aligned with Sustainable Development Goal (SDG) 12 to ensure sustainable consumption and production patterns. Chan, Weitz, Persson, and Trimmer, 2018)